THE IMPACT OF INTERNS TOWARDS CUSTOMER SATISFACTION: A CASE OF BULGARI RESORT AND RESIDENCES BALI, INDONESIA - Tjiputra, Calvin (Directorate of Academic Research and Community Services, 2019)
The main objective of this research study is to investigate the impact that interns create towards the customer satisfaction of a certain company, which in this case Bulgari Resort and Residences, Bali, Indonesia. The steps that the author took for this research are these following; analyzing literature review and previous studies to backup and support the study, and then the author collects necessary data needed for the research by utilizing questionnaires. Afterwards, the author proceeds to process the data gathered using SPSS to generate the result to answer the main question of the study. The result obtained through this research states that intern does have significant impact towards the customer satisfaction level of Bulgari Resort and Residences, Bali, Indonesia.